(3GdfhGOQ hGdRjGQGJ Ydi eG aj GdeOhfI hZjQgG ef GdCegGJs - (3YHO Gddg Hf YHO GdQMef GdfaRi GdbjQhGfi GdeGdcj , CHh eMeO , GHf CHi RjO , J (B386 (3g`s; (3CHh YHO Gddg YHO GdQMef Hf GdbGSe GdeGdcj, CHh YHO Gddg,J (B191 (3g` s
(3ChdgG (B:s
(3Ghd GdLRA GdKGdK ef cJGH GdhUGjG s
(3BNQgG (B:s
(3GdgHGJ hGdUObGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B10 - (3U (B283 s
(3eUOQ GbJfGA GdCUd (B:s
(3CjGUhajG (B(1494) s
Keywords: (3Gdabg GdeGdcjs